Changes in cold-pressed oil due to roasting of hazelnut kernels - Radovanović Mirjana; Kurtić Jelena; Petković Marko; Miletić Nemanja; Đurović Vesna (Acta Agriculturae Serbica)
Hazelnut oil is a high-quality nutritional product, especially the oil obtained by cold pressing. Cold-pressed oils generally retain the original chemical composition and nutritional value of the hazelnut kernel. Due to the presence of unsaturated fatty acids, hazelnut oil is subject to oxidative and thermo-oxidative changes depending on whether the oil or kernels have been subjected to inappropriate storage or heat treatment. In this study, the influence of roasting hazelnut kernels at 180 °C for 24 minutes on cold-pressed oil was investigated. Roasting hazelnut kernels caused an increase in acid value in cold-pressed oil, which could indicate hydrolytic changes in triacylglycerols. There was a decrease in the refractive index, which also indicates changes in triacylglycerols and fatty acids. Roasting the kernels had no effect on the content of water and volatile matter. No peroxides were detected either, regardless of whether the kernels were subjected to heat treatment. However, it is clear from the specific absorbance values that the roasting of the hazelnut kernels initiated oxidative processes, and the change in the UV/Vis spectrum clearly indicates that the heat treatment of the kernels led to a deterioration of the oil, possibly as a result of changes in unsaturated bonds. However, the quality parameters of the cold-pressed oil from heat-treated kernels, i.e., the water and volatile matter content as well as the acidity and peroxide values, are in accordance with the regulations, as the changes in these parameters were minor or non-existent.